The Role of Community Police Officer’s Counseling in Preventing the Criminal Action of Burglary in the Jurisdiction of the Boyolali Police Resort - William Simbolon (Indonesian Journal of Police Studies, 2022)
This research is motivated by the high rate of burglary that occurred in the jurisdiction of the Boyolali District. Police has the duty and authority to maintain the security and public order, enforcing the law, and taking responsibility of protection and giving service to the community. The aim of this study is to analyze the role of community police officer in preventing the occurrence of the burglary case and the factors that affect the performance of community police officer, and also the method to optimize the role of community police officer in Boyolali District. This research was conducted using a qualitative approach and data collection techniques through observation, document study and interview to provide an overview of community police officer Boyolali District’s role in preventing burglary case. The theory that used for data processing is the theory of roles, management theory and SWOT theory. The results of the study shows that the role of community police officer in Boyolali District has not run optimally in burglary case prevention. This is influenced by factors internal and external. The lack of human resources and poor organization is the main internal factor that causes the prevention activities are not implemented optimally. The Covid-19 situation become the main external factor that makes it difficult to gather the community for counseling and educating in preventive actions purposes. The author suggests to increase the quality and quantity personnel of Boyolali’s community police officer resort by giving vocational training and education to increase the resources Boyolali’s community police officer. Increase the number of community police officer personnel in order to achieve the ideal conditions of one community police officer in one village so that they can work optimally to prevent criminal acts of burglary.